Transcatheter aortic valve replacement with or without anesthesiologist: results from a high-volume single center. Issue 12 (7th December 2022) - Angelillis, Marco; Stazzoni, Laura; Costa, Giulia; Giannini, Cristina; Primerano, Chiara; Spontoni, Paolo; Pieroni, Andrea; Guarracino, Fabio; Bertini, Pietro; Baldassarri, Rubia; De Carlo, Marco; Petronio, Anna S.
Abstract : Aims: Local instead of general anesthesia has become the standard approach in many centers for transfemoral transcatheter aortic valve replacement (TAVR). New generation devices and an increase in operator skills had led to a drastic reduction in periprocedural complications, bringing in the adoption of a minimalist approach. In our study, we aimed to compare patients treated with TAVR under local anesthesia with or without the presence of an anesthesiologist on site (AOS). Methods: We compare procedural aspects and results of patients treated with TAVR with an AOS against patients treated with TAVR with an anesthesiologist on call (AOC). From January 2019 to December 2020, all consecutive patients undergoing transfemoral TAVR with either the self-expandable Evolut (Medtronic, MN, USA) or balloon-expandable SAPIEN 3 (Edwards Lifesciences, CA, USA) were collected. Results: Of 332 patients collected, 96 (29%) were treated with TAVR with AOS, while 236 (71%) were treated with TAVR with AOC. No differences in procedural time, fluoroscopy time and amount of contrast medium were observed. No procedural death and conversion to open-chest surgery was reported. The rate of stroke/transient ischemic attacks and major vascular complications was similar in the two groups. No patients in both groups required conversion to general anesthesia. Two patients (0.8%) in the AOC group required urgent intervention of the anesthesiologist. In the AOC group, there was a greater use of morphine (55.9% vs. 33.3%, P  = 0.008), but with a lower dose for each patient (2.0 vs. 2.8 mg, P  = 0.006). On the other hand, there was a lower use of other painkiller drugs (3.4% vs. 20.8%, P  = 0.001). No difference in inotropic drugs use was observed. Conclusion: In patients at low or intermediate risk undergoing transfemoral TAVR, a safe procedure can be performed under local anesthesia without the presence of an anesthesiologist in the catheterization laboratory.